KESULITAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI PECAHAN PADA SISWA KELAS V SDN 188 PEKANBARU - Ummu Haniq (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This research is motivated by the large number of students who have difficulty in solving mathematical problems of with fractions. This research aims to find out and describe the difficulties experienced by student in solving mathematical problem in fraction. This type of research is qualitative research. This Study found that the difficulties experienced by students in solving fractions are difficulty in understanding the concept of fractional counting operations, difficulty because it does not master multiplication as a preparatory material, and difficulty in solving problem solving problems in fractions. Internal factors that cause students to have difficulty in solving math problems in fraction are low student motivation, students don’t like math, and low ability of students in mathematics. External factors that cause students to experience difficulties in fraction learning are unfavorable class conditions and poor classroom management.